KOMPETENSI MANAJERIAL DAN KOMITMEN MANAJEMEN PADA KETERBERDAYAAN KARYAWAN DALAM MENCAPAI KINERJA PERUSAHAAN - Ratmawati, Dwi (JURNAL BISNIS STRATEGI, 2008)
The shifting of a management paradigm, due to the fast development on management science, urges an organization or a company to conduct change in the management style. Recently this style appreciates very much on the value of an intellectual capital. An intellectual capital, Ulrich (1998) states, has two important characteristics, indeed a competency and a commitment. This research considers a competency and a commitment from a managerialpoint of view. In this regard, the competency refers to a managerial competency and the commitment refers to managerial commitment to the employee empowerment. These two characteristics have been the key success factors in a competitive business era. Uke other businesses, banking industries experience the similar situation, hence a very tight competition. Accordingly, banking industries have to focus on a service quality. In these regards, banking management has to evaluate regularly and must understand what the real needs of their customers. In order to achieve its goals and high performance quality, banking management cannot solely focus on the managerial competency, but they must also pay more attention on managerial commitment, particularly the employee empowerment. This research is aimed at examining the impact of managerial competency and commitment to the employee empowerment, and in turns its impact on the company performance. This idea is then built into a model which includes two intervening variables, indeed employee empowerment and employee satisfaction. In addition, the model is also linked to an external environment as a moderating variable. The respondents are supefVisors who work in bank companies which are known to have a very good setvce quality (Marketing Research Indonesia, 2005). Among them, eight companies were selected and 206 supervisors took place.The consideration is to delve whether the intellectual capital is optimally made use in the effort to achieve planned company performance. The result indicates that managerial competency and management commitment to employee empowerment respectively affect positively and significantly on the company performance. This result confirms to Pena's (2002), Mavridis' (2004), and Pickett's (1998) studies. In addition, the result supports that the intervening variables strengthen the management commitment in achieving company performance. This result supports the studies of Hickman (1998), Luthans (2002), and Moye (2003). This linkage implies that management commitment to employee empowerment and employee satisfaction is not a normative aspect rather it is very important and a key factor to the success of the companies.Then the test of moderating variable proves that its role on the relationship between two aspects of intellectual capital and company performance does not necessarily influence. This results shows that in some cases, the role of external environment lessen Zahra (1993) and Lumpkin and Dess (2001). This is caused by the respondents are not the decision makers. To explore this relation, it would be better if the questionnaires are aimed at managers rather then supervison.